2015
DOI: 10.3324/haematol.2015.134999
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in TGFB1 is associated with worse non-relapse mortality and overall survival after stem cell transplantation with unrelated donors

Abstract: Hematopoietic stem cell transplantation (HSCT) is a medical procedure used to treat malignant and non-malignant diseases of the blood, as well as solid tumors. The outcome of HSCT is influenced both by clinical and genetic factors. Compatibility between the recipient and the donor in terms of HLA is a wellknown limiting factor for the success of allogeneic HSCT.1 In addition, genes other than those of the HLA system, in particular those that are highly polymorphic, have been proposed as potential factors affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
0
11
1
5
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Of the 7 articles whose findings we attempted to replicate, 2 articles tested multiallelic models in NOD2/CARD15 5 and CCR5 Figure 2; supplemental Table 3). Figure 2.…”
Section: Replicationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Of the 7 articles whose findings we attempted to replicate, 2 articles tested multiallelic models in NOD2/CARD15 5 and CCR5 Figure 2; supplemental Table 3). Figure 2.…”
Section: Replicationmentioning
confidence: 99%
“…A recent publication from Anthony Nolan showed that the p001 haplotype including the C allele at +29 position, so called 'high producers' patients, had a significant reduction in OS due to an increase in NRM. 49 Our study has strengths. It is one of the largest cohorts reported in this topic.…”
Section: Discussionmentioning
confidence: 96%
“…For this reason we We had to take into consideration that genetic TGFB1 variants are arranged in well-defined haplotypes: −1347T (rs1800469) allele is linked to +29C (rs1982073, +29T>C; L10P), and +74G (rs1800471; +74G>C; R25P), forming the second most common TGFB1 haplotype (called p001, frequency: 30%). Serum TGFβ1 levels and surface expression on regulatory T-cells as latency associated peptide are reported generally higher in the presence of −1347T and +29C variants [16,21]. The haplotype known as p003 [−1347C, +29T, +74G] is the most common among Caucasians with a frequency of 54% [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…Several variants, located in the 5′ regulatory and in the signal peptide regions, are responsible for interindividual variations in cytokine secretion and plasma levels. Several studies investigated the effect of functional TGFB1 polymorphisms on the outcome of HSCT, however results were contradictory [12,[16][17][18][19][20]. Resolving the issue, a fine mapping of TGFB1 promoter haplotype structure was performed recently in Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation